Importance of surface drainage management to slope performance. Issue 3 (3rd July 2018) - Lee, Ryan W H; Law, Rachel H C; Lo, Dominic O K
Abstract : The vast majority of the landslides in Hong Kong are triggered by rainfall. Surface drainage commonly provided on man-made slopes aims to prevent surface erosion and reduce infiltration. It plays an important role to avert slope instability. However, inadequate management of surface drainage could hamper its efficiency and often results in uncontrolled surface water flow contributory to landsliding. This paper provides insights on the importance of slope surface drainage management under the dense urban settings in Hong Kong from the landslide perspective. Selected landslides involving inadequately managed surface drainage are presented to highlight the key lessons learnt and areas deserving attention on various drainage aspects, including the design and detailing. It is noteworthy that inadequate surface drainage maintenance could exacerbate and lead to sizeable landslides even on engineered slopes. A review of landslide records over the years suggests that some landslides could have been averted had there been proper surface drainage maintenance.